Michigan Supreme Court historical reference guide - Chardovoyne, David (Michigan State University Press, 2015)
This second edition of the Michigan Supreme Court Historical Reference Guide contains the biographies of Michigan Supreme Court's justices from its territorial beginnings in 1803 through 2015. It includes summaries of twenty top cases of the Michigan Supreme Court, which contextualize the eras in which the justices were on the bench, giving a greater depth of understanding to both who the justices were and the historical significance of the cases they decided. A rich reference for historians and attorneys, this book also includes valuable charts detailing election dates and candidates as well.